2020
DOI: 10.1021/acscatal.0c01614
|View full text |Cite
|
Sign up to set email alerts
|

Current State of [FeFe]-Hydrogenase Research: Biodiversity and Spectroscopic Investigations

Abstract: Hydrogenases are redox enzymes that catalyze the conversion of protons and molecular hydrogen (H2). Based on the composition of the active site cofactor, the monometallic [Fe]hydrogenase is distinguished from the bimetallic [NiFe]-or [FeFe]-hydrogenase. The latter has been reported with particularly high turnover activities for both H2 release and H2 oxidation, notably at neutral pH, ambient temperatures, and negligible electric overpotential. Due to these properties, [FeFe]-hydrogenase represents the 'gold st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
122
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(138 citation statements)
references
References 196 publications
1
122
0
Order By: Relevance
“…A similar downshi of the H ox -signal upon formation of H ox H has recently been reported for Cr HydA1. 9 As comparing spectra of samples prepared at mildly basic and acidic conditions did not reveal signicant changes in the relative amplitudes of the rhombic signals their interconversion appears to be more complicated than an acid-base equilibrium. The structural details of this H ox H-like state in Tam HydS remains to be fully elucidated.…”
Section: Epr Characterization Of Holo-tam Hydsmentioning
confidence: 88%
See 2 more Smart Citations
“…A similar downshi of the H ox -signal upon formation of H ox H has recently been reported for Cr HydA1. 9 As comparing spectra of samples prepared at mildly basic and acidic conditions did not reveal signicant changes in the relative amplitudes of the rhombic signals their interconversion appears to be more complicated than an acid-base equilibrium. The structural details of this H ox H-like state in Tam HydS remains to be fully elucidated.…”
Section: Epr Characterization Of Holo-tam Hydsmentioning
confidence: 88%
“…3,4 Phylogenetically, [FeFe]-hydrogenases can be broadly divided into four main groups, denoted group A, B, C, and D, which in turn contain numerous subclasses. [5][6][7][8][9] Considering the wellconserved nature of the auxiliary proteins involved in cofactor assembly (HydEFG), 6 they all arguably share a dependence on the same hexanuclear iron cofactor, the "H-cluster". This biologically unique cofactor consists of a canonical [4Fe-4S] cluster ([4Fe-4S] H ) connected to a low valent dinuclear iron complex ([2Fe] H ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3B), where a simple C(2)H 2 replaces the C a H-NH 2 of tyrosine. A strong new HPPAderived radical EPR signal was observed, with majority spin density on the C2 carbon: when the HPPA C2 carbon was specifically 13 C-labeled, a strong 13 C-hyperne splitting was observed. Moreover, mass spectrometry of dAdoH with the HPPA reactions run in buffer with natural abundance water versus 2 H-enriched water showed that the abstracted H-atom is not exchangeable with HPPA as a substrate, eliminating the H of the HPPA phenol OH group as the abstracted hydrogen.…”
Section: Hydg and The Radical Mechanism Of Tyrosine Lysismentioning
confidence: 99%
“…1). The [2Fe] H unit, thought to be the site where the H + and H 2 substrates bind and react, [10][11][12][13] harbors the organometallic elements of the H-cluster, with the two irons exhibiting CO and CN terminal ligands, and with two bridges linking these two irons in the form of a third CO along with a unique SCH 2 NHCH 2 S azadithiolate (adt) species. Unlike the [4MnCa] oxygen evolving complex of photosystem II, which self-assembles under illumination in a process termed photoactivation, 14 the complex catalytic Fe-S clusters of enzymes such as these hydrogenases and the nitrogenases must be synthesized enzymatically.…”
Section: Introduction To [Fefe] Hydrogenasementioning
confidence: 99%